2013
DOI: 10.1021/op300344m
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Alternate Synthesis for a Key JAK2 Inhibitor Intermediate via Sequential C–H Bond Functionalization

Abstract: The development of an alternative synthetic route to a functionalized imidazopyridazine which strategically streamlines the synthesis and avoids a number of problematic reagents is described. Key to the success of this alternative route is the use of two C–H functionalization reactions: a Pd-catalyzed direct benzylation reaction to functionalize a C–H bond with a substituted benzyl group and a V-catalyzed NMO addition reaction to install a benzylic morpholine moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
2
15
0
1
Order By: Relevance
“…Imidazopyridazine 22 (Scheme 8 ) with an ethyl ester at C-3 has been extensively studied as an alternative precursor for the NMO/VO(acac) 2 chemistry, although it showed initially poor exo : endo selectivity (3:1) when compared to 1 (not shown). 32 Similarly, poor exo : endo selectivity was observed in this visible light-mediated system giving a 1.1:1 exo : endo ratio and only moderate isolated yield (36% 22 , 19% 24 , not shown). Attempting to improve the exo : endo ratio via the use of the 10:1 DMA:H 2 O solvent conditions employed previously led to no improvement in selectivity (Scheme 8 ).…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Imidazopyridazine 22 (Scheme 8 ) with an ethyl ester at C-3 has been extensively studied as an alternative precursor for the NMO/VO(acac) 2 chemistry, although it showed initially poor exo : endo selectivity (3:1) when compared to 1 (not shown). 32 Similarly, poor exo : endo selectivity was observed in this visible light-mediated system giving a 1.1:1 exo : endo ratio and only moderate isolated yield (36% 22 , 19% 24 , not shown). Attempting to improve the exo : endo ratio via the use of the 10:1 DMA:H 2 O solvent conditions employed previously led to no improvement in selectivity (Scheme 8 ).…”
Section: Resultsmentioning
confidence: 65%
“…The aqueous HCl was basified to pH 12 with NaOH and extracted twice with CH 2 Cl 2 , dried (Na 2 SO 4 ), filtered and concentrated to give 2 (29 mg, 58% recovery, >98% a/a), in accordance with the literature . 32 1 H NMR (500 MHz, CDCl 3 ) δ H 7.62 (1H, t, J 7.9), 7.38 (1H, td, J 0.7, 0.3), 7.30 (1H, dd, J 8.3), 7.12 (1H, dd, J 10.0, 1.9), 4.00 (2H, s), 3.79 (4H, br s), 2.68 (3 H, s) and 2.61 (3H, s).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidative formation of carbon-carbon bonds mediated by vanadium has been reported as a method for the aminomethylation of arenes and heteroarenes. The so far described methods include V 2 O 5 and VO(acac) 2 used for the alkylation of 2-naphthol and nitrogen-containing heteroaromatic moieties containing N-methylmorpholine-N-oxide, tetrahydroisoquinolines, and N,N-dimethylacetamide [107][108][109][110][111][112][113]. The mechanisms involving oxidation of the amine mediated by vanadium to give iminium ions, followed by a nucleophilic attack of the heteroaromatic ring, have been suggested for most reactions.…”
Section: Vanadium-catalyzed C-h Activationmentioning
confidence: 99%
“…Research Laboratories have reported an alternative synthetic route to a functionalized imidazopyridazine intermediate via sequential C-H bond functionalization for the synthesis of JAK2 inhibitor LY2784544 79 that was undergoing clinical trials for the treatment of several myeloproliferative disorders. 28 The previously reported synthesis have several liabilities, including the use of amino acetal to form the pyridazine framework which was not readily available and usage trifluoroacetic acid (TFA) and triethylsilane liability from a waste disposal perspective, among others. 29 Key to the success of this alternative route is the use of two C-H functionalization reactions: a Pd-catalyzed direct benzylation reaction to functionalize a C-H bond with a substituted benzyl group and a V-catalyzed NMO addition reaction to install a benzylic morpholine moiety (Scheme 13).…”
Section: 4a Synthesis Of Ly2784544: Researchers Of Lillymentioning
confidence: 99%